COMPARISON OF MECHANICAL ISOSTRAIN LINES AND X-RAY PENDELLOSUNG FRINGES - Aloumyan, K. V.; Mnatsakanyan, T. C.; Eyramjyan, T. H.; Eyramjyan, F. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2004)
The effect of crystalline disturbances, arising due to dislocations, upon the form of Pendellosung fringes obtained in an X-ray two-block interferometer is considered. It is shown, that for local regions of disloationc Si monocrystals the distribution of Pendellosung fringes coincides with the isostrain lines.